Body mass index in young adulthood and mid-life cardiovascular risk factors in South Asian American adults: The MASALA study - Saihej P. Basra; Sadiya S. Khan; Namratha R. Kandula; Alka M. Kanaya; Nilay S. Shah (Indian Heart Journal, 2023)
The association of self-reported BMI at age 20, at age 40, the highest BMI within the past 3 years, and current BMI with current mid-life cardiovascular risk factors and coronary artery calcium (CAC) was evaluated among 1148 South Asian American participants (mean age 57 years) in the MASALA study. A 1 kg/m2 higher BMI at age 20 was associated with higher odds of hypertension (aOR 1.07, 95% CI 1.03–1.12), pre-diabetes/diabetes (aOR 1.05 [1.01–1.09]), and prevalent CAC (aOR 1.06 [1.02–1.11]) in mid-life. Associations were similar for all BMI measures. Weight across young adulthood is associated with mid-life cardiovascular health in South Asian American adults.